MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA MELALUI PEMBELAJARAN IPA BERBASIS SOCIO-SCIENTIFIC ISSUES PADA MATERI PENCEMARAN LINGKUNGAN - Dimas Galih Kirana; Mohammad Budiyanto; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The purpose of this study was to describe the implementation of learning, students' scientific literacy skills, and students' responsses to learning in the context of socio-scientific issues on environmental pollution material. The type of research used a pre-experimental design with a one-group pretest-posttest design. The target of the research, namely 16 seventh grade students of SMP Negeri 3 Sidoarjo. The data was obtained by observation, tests, and questionnaires using qualitative descriptions and quantitative descriptions. The results showed the average score of learning implementation was 3.46, with a good category. The average score of students' scientific literacy skills on the pretest was 36.63, while the posttest was 62.5 with an increase in students' scientific literacy skills, which was marked by an N-Gain value of 0.41 in the medium category. Students responsded positively to learning in socio-scientific issues on environmental pollution material with a percentage of 96% with a very good category. The conclusion of this research is the learning process in the context of socio-scientific issues on environmental pollution material can improve students' scientific literacy skills.